Influência do comprometimento cognitivo, fenótipo motor e da dupla tarefa em esteira associada a neuromodulação na função executiva e mobilidade funcional em pessoas com doença de Parkinson - Menezes, David Sam Pessoa de (2022)
Introduction: Mild cognitive impairment can be present from the initial phase of PD, and culminates in dysfunction in several domains of executive function. The akinetic-rigid phenotype is related to a greater propensity to develop dementia as the disease progresses. Dual-task training associated with anodic tDCS appears to improve cognitive function in PD. Objective: To investigate whether there is an influence of the phenotype on the functional domains of executive function and mobility of people with PD; To analyze the effects of dual-task training during treadmill gait associated with neuromodulation in improving executive function, functional mobility and motor function in people with Parkinson's disease; Learn about the influence of cognitive impairment levels on response in selective attention and processing speed, semantic memory and mental flexibility in Parkinson's disease. Method: This is a multicenter study that produces three scientific articles: two cross-sectional studies, and a pilot, placebo-controlled, double-blind, randomized clinical trial, carried out at the NeuroMove laboratory at UFPB. For the construction of the primary measurement test (TMT), verbal fluency assessment test (TVF), Montreal Knowledge Assessment Scale (MoCA). For the secondary functional results, the TUG (mobility) 10-meter walk test and the unified assessment scale for Parkinson's disease - MDS-UPDRS II and III (motor function) were used. Estimates were published in two moments: before starting treatment (T0) and after the twelfth session (T1). The 12 intervention sessions were performed three times a week, followed by four weeks. The study was composed of two groups: (1) dual-task training associated with anodic tDCS; (2) simple gait training associated with anodic tDCS. Participants were also stratified for cognitive impairment and motor phenotype ―dominant tremor‖ (TD) and ―gait disorders/postural instability‖ (DMIP). a value of P < 0.05 (chance of error) for the difference between the moments between the initial assessment and the final assessment. Results: The analysis by stratification of the phenotypes showed a significant difference between the phenotypes for TUG, and for the level of anxiety and depression. Stroop demonstrated a positive correlation with TUG-dual task (TUG-DT) and with TMT in the TD phenotype. In the DTs, there was also a positive correlation between MoCA and TFV. There was a negative correlation: between TMT and TFV, between Stroop and TFV and between Stroop and MoCA. For the DMIP phenotype, there was a positive correlation between MDS-UPDRS III and Stroop and between MDS-UPDRS III and TMT. There was a negative correlation: between Stroop and MoCA, between Stroop and TFV, between MoCA and TUG and between MoCA and TMT. Preliminary data from the clinical trial showed that both groups (experimental and control) showed changes in Stroop NC (p=0.039), TMT (p=0.022), TFVA 5s, TFVP 5s (p=0.005), TFVP 60s (p= 0.001) and TUG (p=0.051). There was a significant difference between the groups for the 60s TFVP (p=0.020). Conclusion: The TD and DMIP phenotypes have different characteristics regarding functional mobility and levels of anxiety and depression. The improvement in semantic memory was more expressive in the group submitted to dual task training associated with tDCS. Cognitive impairment seems to influence the performance of executive function domains.